A New Asymptotic-Tolerance Model of Dynamic Problems for Transversally Graded Cylindrical Shells - TOMCZYK, Barbara; SZCZERBA, Paweł (Engineering Transactions, 2017)
The objects of consideration are thin linearly elastic Kirchhoff-Love-type open circular cylindrical shells having a functionally graded macrostructure and a tolerance-periodic microstructure in circumferential direction. The aim of this note is to formulate and discuss a new non-asymptotic averaged model for the analysis of selected dynamic problems for these shells. The proposed asymptotic-tolerance model equations have continuous and slowly varying coefficients depending also on a cell size. An important advantage of this model is that it makes it possible to study micro-dynamics of tolerance-periodic shells independently of their macro-dynamics.